THE EFFECT OF CORPORATE FINANCIAL RATIO UPON THE COMPANY VALUE - Kamilah Sadi’ah (The Accounting Journal of Binaniaga, 2018)
This study aimed to get empirical evidence about the effect of corporate financial ratios consists of return on assets, dividend payout ratio and debt-to equity ratio on the firm value. Firm value uses a price-to book value (PBV) by calculating the price market per share divided by book value per share. Population of this research is the companies listed in LQ45 on the Indonesia Stock Exchange in 2015-2016 which some 45 companies using total sampling technique. Methods of data analysis using descriptive statistical analysis and multiple linear regression. These results indicate that corporate financial ratios consists of return on assets, dividend payout ratio and debt-to equity ratio have a significant effect simultaneously on the firm value. However, partial test results showed that return on assets and dividend payout ratio have a significat effect on the firm value. While the debt-to equity ratio has no significant effect on the firm value.Key words: price-to book value, return on assets, dividend payout ratio, firm value.